A water property right inventory of 60 countries. Issue 2 (4th May 2021) - Bosch, Hilmer J.; Gupta, Joyeeta; Verrest, Hebe
Abstract: Through history, property rights in water have been treated differently worldwide. Given the current global trend promoting water allocation through permits, and the lack of comparative literature on how property rights are changing in the global South, this article asks: How have property rights in water evolved including through granting water use permits in Anglophone and Francophone Africa and Asia? We analyse 220 policies and laws of 60 Anglophone/Francophone African and Asian countries. We conclude that (i) these States have put water in the public domain; (ii) this implies expropriating existing customary, private and riparian water rights, and States are struggling to do this democratically; (iii) having taken 'control' over water, these States then use, among others, permits to allocate water and (iv) the rules of permit allocation may undermine States' ability to reallocate water if the need arises.